Inducible depletion of PI(4,5)P(2) by the synthetic iDePP system in Arabidopsis - Doumane, Mehdi (Nat Plants, 2021)
Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P(2)] is a low abundant membrane lipids essential for plasma membrane function. In plants, mutations in PI4P 5-kinases (PIP5K) suggest that PI(4,5)P(2) production is involved in development, immunity and reproduction. However, phospholipid synthesis is highly intricate. It is thus likely that steady-state depletion of PI(4,5)P(2) triggers confounding indirect effects. Furthermore, inducible tools available in plants, allow to increase but not decrease PI(4,5)P2, and no PIP5K inhibitors are available. Here, we introduce iDePP (Inducible Depletion of PI(4,5)P(2) in Plants), a system for the inducible and tunable depletion of PI(4,5)P(2) in plants in less than three hours. Using this strategy, we confirm that PI(4,5)P(2) is critical for various aspects of plant development, including root growth, root hair elongation and organ initiation. We show that PI(4,5)P(2) is required to recruit various endocytic proteins, including AP2, to the plasma membrane, and thus to regulate clathrin-mediated endocytosis. Finally, we uncover that inducible PI(4,5)P(2) perturbation impacts the dynamics of the actin cytoskeleton as well as microtubule anisotropy. Together, we propose that iDePP is a simple and efficient genetic tool to test the importance of PI(4,5)P(2) in given cellular or developmental responses, but also to evaluate the importance of this lipid in protein localization.